Estimation of air entrainment and aeration efficiencies of weirs using genetic expression programming - Baylar, Ahmet; Unsal, Mehmet; Ozkan, Fahri; Kayadelen, Cafer (Korean Society of Civil Engineers-Ksce, 2014)
The primary purpose of a weir is to measure discharge. Moreover, it can be used as a tool to increase aeration efficiency in rivers, fish hatcheries, and water treatment plants. A free overfall jet from a weir plunging into downstream water causes entrainment of the air bubbles if the free overfall jet velocity exceeds a certain critical value and hence aeration occurs. In recent years, different soft computing systems have been successfully employed for the solution of complex problems. The aim of this study is to develop models to estimate air entrainment and aeration efficiencies of weirs using soft computing systems. For this aim, genetic expression programming, a recently developed artificial intelligence technique, is used. Genetic Expression Programming (GEP) is a genetic algorithm as it uses populations of individuals, selects them according to fitness, and introduces genetic variation using one or more genetic operators. GEP is preferred since it generates a mathematical function which fits to given experimental data. The results indicate that there are good agreements between the measured values and the values obtained by the genetic expression programming models. These good agreements confirm the validity of the developed genetic expression programming models.
Keywords: genetic expression programming; GEP; weir; aeration efficiency; air entrainment rate